Analyzing English Writing Error Of Front Office Department In Sudamala Resort Senggigi - Suputra, I Gede Widya (International Journal of Linguistics and Discourse Analytics, 2024)
English has functioned as a lingua franca to communicate among countries. As an international lingua franca, English should be mastered by all employees who work in the hospitality industry. This Research aims at analyzing types of grammatical errors found in the Front Office department, and finding out the factors causing the hoteliers to commit errors. The type of this research was a descriptive case study with triangulation technique. In the first technique the researcher used a writing project to collect the data, for the second technique the researcher collected the data through questionnaire, and the third technique the researcher used an interview to collect the data. The researcher used a writing project to obtain the data about errors in writing. Questionnaires and interviews were provided to obtain the additional data about how they learned English in their life. The results of this study show that there are 110 errors made by the hoteliers. All of the errors are categorized into five types: 1. omission errors (50 errors or 45, 45%), 2. misinformation errors (15 errors or 13,63%), 3. misordering errors (35 errors or 31,8%), 4. overgeneralization errors (10 errors or 9%). Furthermore, the researcher found that there was a perception owned by hoteliers that learning English can be used through translating Indonesian language into English language. This habit created interlanguage errors in their English. The interlanguage error occurred due to over-literal translation conducted by the hoteliers in producing English in which not all words of English can be translated directly into Indonesian language